Concentric-Tube Heat Exchanger Laboratory Setup – Functional Extensions and Preliminary Tests toward a Layered Control Structure - Bartecki, Krzysztof (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The paper presents the adaptation and functional extension of a laboratory setup equipped with a concentric-tube heat exchanger for research and educational applications in heat-exchange process control. The introduced hardware and software modifications enable the implementation of a hierarchical, multi-layer control structure representative of industrial heat exchanger systems. As part of the direct control layer, discrete PI controllers were developed to stabilize the key input process variables of the heat exchanger: heating water temperature, heating water flow rate, and heated water flow rate. The controllers were implemented in a real-time Matlab/Simulink environment and experimentally validated on the laboratory setup. The obtained results confirm satisfactory dynamic performance of the control loops and reveal mutual interactions between them. Using the developed control system, steady-state characteristics and temperature distributions of the heat exchanger were experimentally determined. The results confirm both the nonlinear behavior of the process and its distributed-parameter character. Finally, a conceptual design for a supervisory control layer to regulate the outlet temperature of the heated water is proposed. The presented setup constitutes a versatile platform for future experimental studies on hierarchical control structures and advanced control algorithms for heat exchangers.